Temperature of embryo culture for assisted reproduction - Baak, Nora A (Cochrane Database Syst Rev, 2019)
BACKGROUND: 'Infertility' is defined as the failure to achieve pregnancy after 12 months or more of regular unprotected sexual intercourse. One in six couples experience a delay in becoming pregnant. In vitro fertilisation (IVF) is one of the assisted reproductive techniques used to enable couples to achieve a live birth. One of the processes involved in IVF is embryo culture in an incubator, where a stable environment is created and maintained. The incubators are set at approximately 37°C, which is based on the human core body temperature, although several studies have shown that this temperature may in fact be lower in the female reproductive tract and that this could be beneficial. In this review we have included randomised controlled trials which compared different temperatures of embryo culture. OBJECTIVES: To assess different temperatures of embryo culture for human assisted reproduction, which may lead to higher live birth rates. SEARCH METHODS: We searched the following databases and trial registers: the Cochrane Gynaecology and Fertility (CGF) Group Specialised Register of Controlled Trials, the Cochrane Central Register of Studies Online, MEDLINE, Embase, PsycINFO, CINAHL, clinicaltrials.gov, The World Health Organization International Trials Registry Platform search portal, DARE, Web of Knowledge, OpenGrey, LILACS database, PubMed and Google Scholar. Furthermore, we manually searched the references of relevant articles and contacted experts in the field to obtain additional data. We did not restrict the search by language or publication status. We performed the last search on 6 March 2019. SELECTION CRITERIA: Two review authors independently screened the titles and abstracts of articles retrieved by the search. Full texts of potentially eligible randomised controlled trials (RCTs) were obtained and screened. We included all RCTs which compared different temperatures of embryo culture in IVF or intracytoplasmic sperm injection (ICSI), with a minimum difference in temperature between the two incubators of ≥ 0.5°C. The search process is shown in the PRISMA flow chart. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial eligibility and risk of bias and extracted data from the included studies; the third review author resolved any disagreements. We contacted trial authors to provide additional data. The primary review outcomes were live birth and miscarriage. Clinical pregnancy, ongoing pregnancy, multiple pregnancy and adverse events were secondary outcomes. All extracted data were dichotomous outcomes, and odds ratios (OR) were calculated with 95% confidence intervals (CIs) on an intention‐to‐treat basis. We assessed the overall quality of the evidence for the main comparisons using GRADE methods. MAIN RESULTS: We included three RCTs, with a total of 563 women, that compared incubation of embryos at 37.0°C or 37.1°C with a lower incubator temperature (37.0°C versus 36.6°C, 37.1°C versus 36.0°C, 37.0° versus 36.5°C). Live birth, miscarriage, clinical pregnancy, ongoing pregnancy and multiple pregnancy were reported. After additional information from the authors, we confirmed one study as having no adverse events; the other two studies did not report adverse events. We did not perform a meta‐analysis as there were not enough studies included per outcome. Live birth was not graded since there were no data of interest available. The evidence for the primary outcome, miscarriage, was of very low quality. The evidence for the secondary outcomes, clinical pregnancy, ongoing pregnancy and multiple pregnancy was also of very low quality. We downgraded the evidence because of high risk of bias (for performance bias) and imprecision due to limited included studies and wide CIs. Only one study reported the primary outcome, live birth (n = 52). They performed randomisation at the level of oocytes and not per woman, and used a paired design whereby two embryos, one from 36.0°C and one from 37.0°C, were transferred. The data from this study were not interpretable in a meaningful way and therefore not presented. Only one study reported miscarriage. We are uncertain whether incubation at a lower temperature decreases the miscarriage (odds ratio (OR) 0.90, 95% CI 0.52 to 1.55; 1 study, N = 412; very low‐quality evidence). Of the two studies that reported clinical pregnancy, only one of them performed randomisation per woman. We are uncertain whether a lower temperature improves clinical pregnancy compared to 37°C for embryo incubation (OR 1.08, 95% CI 0.73 to 1.60; 1 study, N = 412; very low‐quality evidence). For the outcome, ongoing pregnancy, we are uncertain if a lower temperature is better than 37°C (OR 1.10, 95% CI 0.75 to 1.62; 1 study, N = 412; very low quality‐evidence). Multiple pregnancy was reported by two studies, one of which used a paired design, which made it impossible to report the data per temperature. We are uncertain if a temperature lower than 37°C reduces multiple pregnancy (OR 0.80, 95% CI 0.31 to 2.07; 1 study, N = 412; very low‐quality evidence). There was insufficient evidence to make a conclusion regarding adverse events, as no studies reported data suitable for analysis. AUTHORS' CONCLUSIONS: This review evaluated different temperatures for embryo culture during IVF. There is a lack of evidence for the majority of outcomes in this review. Based on very low‐quality evidence, we are uncertain if incubating at a lower temperature than 37°C improves pregnancy outcomes. More RCTs are needed for comparing different temperatures of embryo culture which require reporting of clinical outcomes as live birth, miscarriage, clinical pregnancy and adverse events.